Legal Gaps in Apartment Law: The Gading Nias Case and Urban Spatial Planning Challenges - Gultom, Ruth Elita; Ikramuddin, Said (Indonesian Journal of Agrarian Law, 2024)
This paper investigates the legal complexities in implementing the Apartment law within the Gading Nias Residence, one of the largest and densest vertical housing complexes in North Jakarta. The Apartment law, which distinguishes between individual ownership of apartment units and collective ownership of common areas and land, has faced significant challenges in this context. These challenges include delays in the formation of the Association of Apartment Owners and Occupants (PPPSRS), conflicts between residents and developers, and ambiguity surrounding land rights, which has left many residents without legal certainty regarding their units. Through a normative legal approach, combined with empirical case studies, this research examines the relevant laws and regulations, as well as the practical legal issues encountered on the ground. The study also explores the broader implications of these legal challenges on urban spatial planning, with particular emphasis on zoning inconsistencies, infrastructure strain, and the relationship with the Agrarian Reform policy under Presidential Regulation No. 62 of 2023. The analysis identifies weak government oversight and legal indecisiveness in the implementation of collective land rights as key contributors to the legal issues in Gading Nias. The paper concludes by recommending enhanced government oversight, accelerated land rights certification, and increased legal awareness among residents as critical solutions. This research contributes to the development of more effective legal frameworks and governance structures for vertical housing in Indonesia, highlighting the urgency of addressing these gaps amid rapid urbanization.